Lichen striatus in a child after immunization - Dragoš, Vlasta (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2006)
Lichen striatus is a self-limited, lichenoid eruption particularly common in children. The lesions are located on extremities and less commonly on the trunk, and they follow the developmental lines of Blaschko. The etiology of lichen striatus is as yet unknown. It has been observed after infection or immunization in atopic patients and in siblings. The authors report on a 15-month-old girl that developed lichen striatus along the Blaschko lines on the trunk and one extremity after receiving the combined vaccine against measles, mumps, and rubella. Six months later, complete resolution of the skinlesions occurred without any treatment, leaving only slightly hypopigmented macules on the extremity.
Keywords: Adverse Effects; baby; Dojenček; Immunization; Imunizacija; Infant; Lichenoid Eruptions; Lihenoidni izpuščaji